STATE DOT ENVIRONMENTAL AND ECONOMIC BENEFITS OF RECYCLED MATERIAL UTILIZATION IN HIGHWAY PAVEMENTS - Del Ponte, Kelly L. (My University, 2016)
The use of recycled materials in highway construction has the potential to achieve significant benefits affecting the triple-bottom line (environment, prosperity and society). Although state departments of transportation (DOTs) have been in the forefront of introducing recycled materials infrastructure projects, it has been challenging to clearly convey the benefits in a quantitative and transparent manner using easily understood metrics. What is lacking is direct information on sustainability assessment characteristics, i.e. greenhouse gas emissions, energy and water consumption and waste generation. To determine the benefits of using recycled materials for DOTs, the Recycled Materials Resource Center (RMRC) conducted life cycle assessments (LCA) and cost analyses using recycled material quantities provided by six member state DOTs; Georgia (GDOT), Illinois (IDOT), Minnesota (MnDOT), Pennsylvania (PennDOT), Virginia (VDOT) and Wisconsin (WisDOT). PaLATE was used as the LCA analysis tool, after researching other publicly available tools to find an optimal analysis. Four environmental parameters (energy use, water consumption, carbon dioxide emissions and hazardous waste generation) showed percent reductions ranging between 70 and 99 percent when states used recycled industrial byproducts such as fly ash, and recycled roadway materials such as recycled concrete aggregate (RCA) and recycled asphalt pavement (RAP). The cost analysis indicated potential savings of up to 17 million dollars. Any future research into sustainability assessment measurements should consider real time collection of the data, particularly in relation to virgin versus recycled material prices. Further case studies and developments using a material tracking tool developed by the RMRC and presented in this report can aide in determining project specific parameters, and therefore, more accurate future estimations of the economical and environmental of using recycled materials in highway pavements.